Cytotoxic coumaric acid dervatives from premna serratifolia l. on human colon cancer cell dld-1 - Hoang , Minh Hao; Pham, Thi Bich Van (Journal of Technical Education Science, 2017)
The dried leaves (2 kg) of Premna serratifolia L. (Verbenaceae) were exhaustively extracted in methanol then filtered and evaporated under reduced low pressure. The crude extract was subjected to colunm chromatography (CC) with gradient elution (petroleum ether, chloroform, and butanol). The petroleum ether extract has been studied in chemical constituents and biological activity. Three compounds, namely, methyl trans-4-methoxycinnamate (1), methyl trans-4-hydroxycinnamate (2) and methyl caffeate (3) have been isolated from this extract by using colunm and thin layer chromatographies. The chemical structures of pure compounds were elucidated by using 1D and 2D-NMR spectroscopies in comparision with published data. The cytotoxicity of these compounds was evaluated on human colon cancer cell line DLD-1. The results showed a significant cell inhibition. Among the tested substances, methyl caffeate (3) exhibited the strongest cytotoxicity toward DLD-1 (IC50 = 66 mM).